Cultivate or rent out? : land security in rural Thailand - Giné, Xavier (Policy research working paper, 2005)
"In the 1980s the Thai government tried to legalize squatters by issuing special titles that restricted the sale and rental of the land. Using data from 2,874 farming households collected in 1997, the author finds that in places where these government titles where issued, leased plots are more likely to be titled than those that are self-cultivated. For these areas, he uses a model to estimate a 6 percent risk premium in the rental rate for untitled plots. In other areas, however, land rights play no role in the decision to lease land and the rental rate of untitled plots does not include a risk premium. The results indicate that this policy distorted the land rental market by triggering a sense of insecurity among landowners. "--World Bank web site